FACTORS THAT INFLUENCE THE SUCCESS OF IMPLEMENTING TOTAL QUALITY MANAGEMENT (TQM) IN MICRO, SMALL AND MEDIUM ENTERPRISES (MSMEs) IN INDONESIA - Yogasnumurti, Raras Risia; Napitupulu, Rizal Afif A; Setiagraha, Dika (Jurnal Manajemen, 2024)
The business competition experienced by MSMEs in Indonesia is getting tighter and requires MSMEs to maximize their potential. Facing the challenges faced by MSMEs, implementing Total Quality Management (TQM) is a strategy that can be implemented. This research aims to analyze the factors that influence the success of implementing Total Quality Management (TQM) in MSMEs in Indonesia. The method used in this research is a qualitative approach, where the data obtained is based on literature review and previous research sourced from books, journals and websites. The results of the analysis show that there are several factors that influence the success of implementing TQM in MSMEs in Indonesia, namely focus on customers; continuous improvement; teamwork and engagement; top management commitment and recognition; training and development; quality systems and policies; leadership; communication within the company; supplier relationships and management; measurement and feedback; cultural changes in employee behavior and attitudes; and employee empowerment. By paying attention to all these factors, MSMEs in Indonesia can create an environment that supports TQM success, increase competitiveness or compete more globally, reduce dependence on imports, strengthen Indonesia's overall economic position, and achieve the desired sustainability.